Rice seedlings grown under high ammonia do not show enhanced defence responses. (20th October 2021) - Zhou, Heng; Zhou, Ying; Zhai, Fengchao; Wu, Ting; Xie, Yanjie; Xu, Guohua; Foyer, Christine H.
Abstract: Urea‐based fertilizers are commonly used in the agricultural rice production. Urea produces gaseous ammonia upon contact with plants and soil. Although rice is considered to be a relatively ammonium‐tolerant crop, urea fertilization can have a negative impact on seedling establishment because of tissue ammonia accumulation. We investigated the molecular/genetic regulation of ammonia tolerance in rice using a multidisciplinary approach consisting of high‐resolution LC‐MS/MS analysis and bioinformatics, together with plant molecular physiology and biochemistry. Growth with 10 or 80 mM NH4 Cl led to an inhibition of photosynthesis and ROS accumulation. Proteomic analysis revealed changes in the levels of 266 proteins, which function in translation and protein metabolism, amino acid and carbon metabolism/transport, antioxidant and redox metabolism. The abundance of the transcripts encoding these proteins was increased under high ammonium. Data are presented showing that ammonia‐induced changes in metabolism are linked to a strong antioxidant response but little change in secondary metabolism. Abstract : We investigated the molecular/genetic regulation of ammonia tolerance in rice using a multidisciplinary approach consisting of high‐resolution LC‐MS/MS analysis and bioinformatics, together with plant molecular physiology and biochemistry. Proteomic analysis revealed changes in the levels of 266 proteins, which function in translation and protein metabolism, amino acid and carbon metabolism/transport, antioxidant and redox metabolism. The abundance of the transcripts encoding these proteins was increased under high ammonium. Data are presented showing that ammonia‐induced changes in metabolism are linked to a strong antioxidant response but little change in secondary metabolism.